Investigating client’s benefit and client’s fulfillment by preparing cost sheet and cost assurance: A study on Amrita consumer food products ltd. Barisal - Halder, Antara (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2020.